On the strength and failure mechanism of confined pre-holed jointed rock mass via DIC - Wei Wang; Wei Wang; Yundong Bi; Shuo Yang; Shuo Yang (Frontiers in Earth Science, 2025)
As the development of deep underground engineering in modern days (i.e., exploitation of geo-energy and underground constructions), a higher demand arises for an accurate prediction of ground deformation and stability. For jointed rock mass with anisotropy, stress field and the structure of surrounding rock mass change with the underground construction, for example, during deep-ground tunnel excavation which is associated with ground depth and joint angles. Currently, it is difficult to reasonably predict localized deformation of jointed rock mass with existing theory. In this paper, characteristics of strength and failure mechanism of pre-holed jointed rock mass is experimentally investigated by adopting the digital image correlation and acoustic emission methods. The role of buried depth is considered with confining boundary applied during experiments. To precisely characterize deformation patterns and capture cracking via DIC, tests on DIC parameters and analysis algorithms are further carried out. Results show that joint inclination and confining condition exert a notable influence on the mechanical properties and failure behaviour of rock masses with centering holes. Rock mass exhibits ductile failure while applied with a confined boundary. The confining associated with buried depth in practical would pose an influence on the strength of the rock in particular for oblique jointed situations. The perpendicular-jointed condition poses the most significant risk in both shallow and deep buried conditions due to its relatively lower strength and the maintained brittle failure mode.